ANALISIS BAHASA UNTUK KAJIAN SOSIAL: PEMAKNAAN KRITIS TERHADAP PRAKTEK BERWACANA SEBAGAI PRAKTEK SOSIAL - Lukmana, Iwa (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2010)
Social structure and dynamics are to a large extent evidenced in linguistic data. Moreover, linguistic technologisation can serve as an agent of social change. Unfortunately, linguistic data and the accompanying analytical methods developed by linguists appear to be largely ignored by social analists. This article attempts to demonstrate that linguistic analysis, more specifically discourse analysis, can be used as one of the methods of social investigation. This contribution is illustrated through several research studies dealing with hierarchy, bias, and identity. This article also discusses some implications of critical analysis of texts, especially for citizenship and education.